Inception and Evolution of La Corona Lava Tube System (Lanzarote, Canary Islands, Spain). Issue 6 (13th June 2022) - Tomasi, I.; Massironi, M.; Meyzen, C. M.; Pozzobon, R.; Sauro, F.; Penasa, L.; Santagata, T.; Tonello, M.; Santana Gomez, G. D.; Martinez‐Frìas, J.
Abstract: Growing interest in studying large terrestrial lava tubes is motivated in part by their analogy with their extra‐terrestrial counterparts. However, on Earth, the formation of such structures is still poorly understood. Here, the lava tube system of La Corona (Lanzarote, Canary Islands, Spain) is studied to identify how pre‐existing stratigraphy can govern a lava tube's evolution. Combining terrestrial laser scanner technology with field observations and geochemical analyses of the pre‐existing lava enabled us to reconstruct the three‐dimensional geometry of the lava tube system, the paleo‐surface trough which it developed, and the volcanic series into which it carved its path. We show that a pyroclastic layer played a key role in the development of the lava tube. The layer—Derived from late Quaternary Strombolian activity—Is traceable along almost the full length of the tube path and defines the paleo‐topography. The excavation process mostly happens because of the mechanical strength of the substrate, that controls the widening of the growing lava tube. Other influential parameters controlling erosion include slope variations of the paleo‐surface (i.e., knickpoints), and the lava physical properties. Since weak layers such as regolith are a common feature of extra‐terrestrial lava flows, the processes seen at La Corona to the may be highly relevant to the development of planetary lava tube systems. Plain Language Summary: Lava tubes are a promising subject for future planetary exploration. Within this framework, improved knowledge of how these lava caves form and evolve in the post‐cooling phase is crucial. The best way to achieve such insights is to focus on their terrestrial analogs on volcanic islands (i.e., Canary Islands, Hawai'i, Iceland, etc.). Here we study the large lava tube complex of La Corona (Lanzarote, Canary Islands) to constrain the different stages of its development. Its genesis depended on the presence of a weak pyroclastic layer, favoring its initial emplacement. Its subsequent development depended largely on the duration of the thermal contact and the mechanical interaction between molten lavas and pre‐existing lava flows, as well as the paleo‐topography emphasized by the pyroclastic layer and also by the chemical and physical properties (e.g., solidity, state of weathering) of the pre‐existing lava pile. The presence of a weak layer as observed at the La Corona tube system is of interest for understanding the processes by which extra‐terrestrial lava tubes develop among lava sequences where weak layers such as ash layer, rubble and complex ancient surface are likely to be commonly found. Key Points: The presence of a weak pyroclastic layer in pre‐existing lava flows favors the enlargement of lava tubes on Earth The excavation process of lava tubes is enhanced by the thermo‐mechanical erosional action of molten lavas at bedrock knickpoints The large lava tube at La Corona may provide analogs for extra‐terrestrial lava tube structures